2009
DOI: 10.1021/ja808836b
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of the Light-Color Modulation Mechanism of Firefly (Beetle) Bioluminescence

Abstract: To reveal the light-color modulation mechanism of firefly (beetle) bioluminescence, we investigated the spectroscopic properties of the phenolate anion 1-O(-) generated from 5,5-dimethyloxyluciferin (1-OH) using various base/solvent combinations. Phenolate anion 1-O(-) is a model compound for the keto form of wild-type oxyluciferin phenolate anion (OL(-)), which is postulated to be the emitter of the bioluminescence. The fluorescence maxima of 1-O(-) were found to depend on the base/solvent combination used, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
268
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(294 citation statements)
references
References 85 publications
22
268
3
1
Order By: Relevance
“…[20] Calculations by Nakatani et al [21] discarded the resonance-based structure as an explanation, as was corroborated by our own time-dependent DFT (TD-DFT) calculations. [22] Also, several TD-DFT calculations [22][23][24] demonstrated that interaction of a cation with the benzothiazole moiety of OxyLH 2 results in a blueshift, thus refuting the hypothesis formulated by Hirano et al [18] Theoretical [25] and experimental [18] studies also discarded the hypothesis formulated by Nakatsu et al, [17] which stated that the rigidity of the active site modulates the color of light emitted. More recently, we began to pursue clarification of this topic, having reviewed computational studies on multicolor bioluminescence.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…[20] Calculations by Nakatani et al [21] discarded the resonance-based structure as an explanation, as was corroborated by our own time-dependent DFT (TD-DFT) calculations. [22] Also, several TD-DFT calculations [22][23][24] demonstrated that interaction of a cation with the benzothiazole moiety of OxyLH 2 results in a blueshift, thus refuting the hypothesis formulated by Hirano et al [18] Theoretical [25] and experimental [18] studies also discarded the hypothesis formulated by Nakatsu et al, [17] which stated that the rigidity of the active site modulates the color of light emitted. More recently, we began to pursue clarification of this topic, having reviewed computational studies on multicolor bioluminescence.…”
Section: Introductionmentioning
confidence: 88%
“…[13] Several hypotheses have been advanced over the years to try to explain this phenomenon. Keto-enol tautomerism, [14] rotation about a CÀC bond, [15] resonance-based structure, [16] rigidity of the active site, [17] and interaction of the emitter with a cation [18] have all been proposed, but were rejected because they cannot explain the multicolor variation. Branchini et al demonstrated that the keto form of OxyLH 2 suffices for multicolor bioluminescence, [19] and theoretical calculations demonFirefly luciferase exhibits a color-tuning mechanism based on pH-induced changes in the structure of the active site.…”
Section: Introductionmentioning
confidence: 99%
“…This finding together with the acurracy of the calculated absorption and emission maxima indicate that the well-known trend that hybrid functionals give more accurate excitation energies than pure functionals does not apply for bilin The characteristic glow of a firefly is created by a bioluminescent reaction inside the active pocket of the enzyme firefly luciferase. In this reaction, the enzyme catalyzes a conversion of the ground-state heterocyclic acid D-luciferin into the [35][36][37] and spectroscopic [38,39] studies have proposed that the phenolate-keto-OxyLH − form is the light emitter, Naumov and coworkers [40] have recently reported experimental data favoring an enolate species (enolate-OxyLH − or OxyL 2− ). In Paper III, the most probable form as the light emitter was predicted based on the intrinsic tendency of the light emitter to prefer a particular form of OxyLH 2 in aqueous solution at pH 7.…”
Section: Paper IImentioning
confidence: 99%
“…Recent studies favor the dependence of color on the polarization of the emitter oxyluciferin and the degree of covalent interaction between oxyluciferin and luciferase. 46,47 A small shift of kmax is generally attributed to the local polarity changes in the emitter sites. 48,49 The polarizability of the introduced residue is positively correlated to red shift.…”
Section: Bioluminescence Emission Spectra Of Mutant Luciferasesmentioning
confidence: 99%